Turismo de aventura y oferta turística en la Parroquia San Luis de Pambil, Cantón Guaranda. - Rea Rochina, Angel David (2022)
The following research has as its main objective to determine the influence of adventure tourism in the tourist offer of the parish of San Luis de Pambil, Guaranda canton. The research type used is exploratory, descriptive, correlational, explanatory and the design is non-experimental and transversal. In order to apply the surveys, the population used as a population were representatives of the decentralized autonomous government of the parish of San Luis de Pambil and tourists with the help of the survey technique and the questionnaire instrument. The statistical program SPSS version 25 was used for the tabulation of the results, which allowed the reliability of the Cronbach's alpha instrument and the testing of the general hypothesis and the three specific hypotheses under the application of the Chi-square statistic. Finally, the design of an adventure route was carried out in order to generate a tourist offer to provide a better economy in the locality.